Revisiting Mouse Peritoneal Macrophages: Heterogeneity, Development, and Function - Cassado, Alexandra dos Anjos; D’Império Lima, Maria Regina; Bortoluci, Karina Ramalho (Frontiers in Immunology, 2015)
Tissue macrophages play a crucial role in the maintenance of tissue homeostasis and also contribute to inflammatory and reparatory responses during pathogenic infection and tissue injury. The high heterogeneity of these macrophages is consistent with their adaptation to distinct tissue environments and specialization to develop niche-specific functions. Although peritoneal macrophages are one of best-studied macrophage populations, only recently it was demonstrated the co-existence of two subsets in mouse PerC, which exhibit distinct phenotypes, functions and origins. These macrophage subsets have been classified according to their morphology as LPMs (large peritoneal macrophages) and SPMs (small peritoneal macrophages). LPMs, the most abundant subset under steady-state conditions, express high levels of F4/80 and low levels of class II molecules of the major histocompatibility complex (MHC). LPMs appear to be originated from embriogenic precursors, and their maintenance in PerC is regulated by expression of specific transcription factors and tissue-derived signals. Conversely, SPMs, a minor subset in unstimulated PerC, have a F4/80lowMHC-IIhigh phenotype and are generated from bone-marrow-derived myeloid precursors. In response to infectious or inflammatory stimuli, the cellular composition of PerC is dramatically altered, where LPMs disappear and SPMs become the prevalent population together with their precursor, the inflammatory monocyte. SPMs appear to be the major source of inflammatory mediators in PerC during infection whereas LPMs contribute for gut-associated lymphoid tissue (GALT)-independent and retinoic acid-dependent IgA production by peritoneal B-1 cells. In the last years, considerable efforts have been made to broaden our understanding of LPM and SPM origin, transcriptional regulation and functional profile. This review addresses these issues, focusing on the impact of tissue-derived signals and external stimulation in the complex dynamics of periton